Image processing in medical applications - Yasrib, Asma; Suhaimi, Mohd Adam (JITI, 2003)
In this article a number of recent developments in medical imaging are outlined, with the focus being on the application of image processing techniques. Medical images are at the core of medical science and an enormous source of information that need to be utilized. Image processing techniques with regards to biomedical images are generally either used for the retrieval of images (Content Based Image Retrieval) or for analysis and modification of images. In this article we give a description of the different applications of image processing in the medical field.